SM-ND DATING OF THE DZHUGDZHUR PRECAMBRIAN ANORTHOSITES - Sukhanov M.K.; Zhuravlev D.Z. (My University, 1989)
The Dzhugdzhur pluton, the largest in the East Asian anorthosite belt, is situated on the south margin of the Aldan shield. Sm-Nd dating of the Dzhugdzhur independent anorthosites indicates their Proterozoic age and, therefore, gives us the opportunity to reconsider the genesis and the petrographic association of all igneous complexes in the Dzhugdzhur district that contain anorthosite. Our data indicate that there is a single multiphase complex, where some rocks are K-feldspathized, possibly as a result of apatite-ore deposition. The contacts with the host granulites are tectonic.
Keywords: Precambrian; Precambrian; Докембрий